Optimization of process parameters for the bioconversion of activated sludge by Penicillium corylophilum, using response surface methodology - Mannan, Sarkar; Fakhru'l-Razi, Ahmadun; Alam, Md. Zahangir (Journal of Environmental Sciences-China, 2007)
The optimization of process parameters for the bioconversion of activated sludge by Penicillium corylophilum was investigated using response surface methodology (RSM). The three parameters namely temperature of 33"C, agitation of 150 r/min, and pH of 5 were chosen as center point from the previous study of fungal treatment. The experimental data on chemical oxygen demand (COD) removal (%) were fitted into a quadratic polynomial model using multiple regression analysis. The optimum process conditions were determined by analyzing response surface three-dimensional surface plot and contour plot and by solving the regression model equation with Design Expert software. Box-Behnken design technique under RSM was used to optimize their interactions, which showed that an incubation temperature of 32.5"C, agitation of 105 r/min, and pH of 5.5 were the best conditions. Under these conditions, the maximum predicted yield of COD removal was 98.43%. These optimum conditions were used to evaluate the trail experiment, and the maximum yield of COD removal was recorded as 98.5%.